Turkey-EU relations: Scrutinising the instability. - Matos, André (2016)
Turkey-EU relations have been object of various studies due to their complexity and instability. Beginning in 1959, Turkey is the country with the longest path towards the European Union, and these decades have been full of ups and downs. This article aims to explore the instability behind these relations, through the understanding of its causes and consequences, as well as providing some thoughts regarding a possible road map to overcome the stalled situationTurkey-EU relations are found nowadays – the 3 C’s solution.